Complex Endovascular Aortic Repair With a Branched Endograft to Revascularize 5 Renovisceral Vessels and an Intercostal Artery in a Marfan Patient. (October 2019) - Eleshra, Ahmed S.; Panuccio, Giuseppe; Rohlffs, Fiona; Scheerbaum, Martin; Tsilimparis, Nikolaos; Kölbel, Tilo
Purpose: To report a case of thoracoabdominal aortic aneurysm (TAAA) repair treated with a multibranched stent-graft including a prophylactic branch for a large intercostal artery in a Marfan patient at risk for spinal cord ischemia (SCI).Case Report: A 43-year-old man with Marfan syndrome presented with a type IV thoracoabdominal aortic aneurysm (TAAA) and history of multiple previous cardiac and aortic operations over the past 28 years. The maximum diameter of the aneurysm was 60 mm. The patient had 2 right renal arteries and 2 reimplanted segmental arteries (1 occluded). With the goal of preserving both right renal arteries and the large intercostal artery, a 6-branch, custom-made stent-graft was planned and manufactured. Bilateral femoral and right brachial artery access was used. The intercostal artery was catheterized and connected to the retrograde branch from a femoral access. Final angiography and predischarge computed tomography angiography (CTA) showed unimpeded flow to all 6 target vessels. The patient was discharged on postoperative day 10 without clinical signs of SCI. Six-month follow-up CTA demonstrated exclusion of the TAAA and patency of all 6 branches.Conclusion: Multibranched endovascular aortic repair with a branch to a large intercostal artery was technically feasible and clinically successful.